Lifeblood, liquidity, and cash transfusions: beyond metaphor in the cultural study of finance. (1st April 2013) - Weston, Kath
Abstract : During the global financial crisis of 2008, descriptions of the crisis and remedies advanced to address it were suffused with references to blood. Metaphors such as lifeblood, liquidity, blood pressure, cardiac arrest, and transfusion were linked and elaborated into organic analogies of cash/credit 'flow' predicated on the conception of a body animated by a closed circulatory system. Attention to the once controversial claims associated with William Harvey's seventeenth‐century 'discovery' of blood circulation can help denaturalize this usage of circulation and demonstrate how organic economic analogies have informed policy recommendations, not always to best effect. The essay concludes by introducing the concept of meta‐materiality to explain why the anthropology of finance must go beyond metaphorical readings of economic discourse if it hopes to understand phenomena such as the literal uses of blood in political protest and the accelerated commodification of blood donation in response to the crisis.